2015
DOI: 10.4238/2015.july.3.6
|View full text |Cite
|
Sign up to set email alerts
|

Allele frequencies of combined DNA index system (CODIS) and non-CODIS short tandem repeat loci in Goiás, Central Brazil

Abstract: ABSTRACT. In studies of human identification, obtaining a high standard of outcomes and satisfactory conclusions are directly related to the use of highly polymorphic molecular markers. In addition to the combined DNA index system (CODIS) group, it is also important to implement non-CODIS markers into the analysis, as they increase the power of discrimination. During the identification process, it is essential to consider the genetic variation among distinct groups of populations, as the allele frequencies 731… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2017
2017
2019
2019

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 8 publications
0
2
0
Order By: Relevance
“…Population data on CODIS STRs in the Shanghai_Han population have been reported and updated for routine forensic applications, such as personal identification and paternity testing. However, extra STRs are needed, since joint analysis of non-CODIS STRs and CODIS STRs has been reported to be significantly informative in identifying problematic kinship cases when a definite conclusion could not be obtained with only the profile of CODIS STRs (Asamura, Fujimori, Ota, & Fukushima, 2007;Rodovalho et al, 2015). Commercial STR kits enable consistency in marker use and allele nomenclature among laboratories and help improve quality control.…”
mentioning
confidence: 99%
“…Population data on CODIS STRs in the Shanghai_Han population have been reported and updated for routine forensic applications, such as personal identification and paternity testing. However, extra STRs are needed, since joint analysis of non-CODIS STRs and CODIS STRs has been reported to be significantly informative in identifying problematic kinship cases when a definite conclusion could not be obtained with only the profile of CODIS STRs (Asamura, Fujimori, Ota, & Fukushima, 2007;Rodovalho et al, 2015). Commercial STR kits enable consistency in marker use and allele nomenclature among laboratories and help improve quality control.…”
mentioning
confidence: 99%
“…In this sense, Poetsch et al (2013) concluded that the number of hypervariable loci available for a genetic linkage analysis is directly associated with the percentage of certainty established during the assessment of the analysis (Børsting et al, 2008;Rodovalho et al, 2015;Zhang et al, 2015). Therefore, it is critical that STR panels provide sufficient security, permitting an accurate and unfailing conclusion regarding the genetic linkage analysis.…”
Section: Introductionmentioning
confidence: 99%